Distribusi dan Margin Pemasaran Ikan Tongkol (Euthynnus affinis) di Lampulo Kecamatan Kuta Alam Banda Aceh - Aziah Rinaldi; Rahmad Diansyah; Irfan Zikri (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Mackarel is a type of fish that has a high enough economic value to be marketed, therefore a good marketing system is needed in marketing Mackarel. This study aims to determine the marketing channels of Mackarel, marketing margins, the value of the share received and the marketing efficiency of each marketing agency involved in marketing Mackarel. The data used are primary data in the form of data obtained through the interview process and secondary data in the form of production data of Mackarel and fish caught in the sea in 2010-2019. The analytical method used is descriptive method, marketing margin and farmer's share to see the value of efficiency. The results of the analysis obtained are: (1) The marketing institutions involved in marketing Mackarel are fishermen, market retailers, TPI retailers and motorized retailers. (2) The research object has different types, namely super-sized Mackarel and medium-sized Mackarel. (3) The distribution of tuna has 4 marketing channels running, with the most efficient marketing channels being channel 2 and channel 3.